KEBIJAKAN PERLINDUNGAN ANAK KORBAN KEJAHATAN SEKSUAL MELALUI PENDEKATAN KEADILAN RESTORATIF DI LAMPUNG UTARA - Irhammudin Irhammudin; Ibrahim Fikma Edrisy (Universitas Muhammadiyah Ponorogo, 2021)
The purpose of this paper is to compare the reasonableness of insurance for children as victims of sexual violations as directed in Act Number 35/2014 on the Revision of Act Number 23/2002 on Youngster Insurance to the treatment of child victims of sexual mistreatment with a therapeutic equity approach as set forth in Act Number 11/2012 on the Adolescent Criminal Equity Framework. This paper is based on the regularization of legal examination. The findings of the investigation show that the protection of children as victims of sexual savagery in Article 71D of Act Number 35/2014 on the Correction of Act Number 23/2002 on Child Security does not completely mirror the treatment with therapeutic equity approach.